Association of electronic device use before bedtime with chronotype, daytime sleepiness, and quality of life in adults - Karasu, Fatma; Polat, Filiz; Ayar, Duygu (Journal of Dependence, 2023)
Objective: This study was carried out to examine the relationship between chronotype, daytime sleepiness and quality of life of adult individuals using electronic devices before sleeping in bed.Method: The population of the descriptive study consisted of individuals over the age of 18 in Turkey. The research was carried out with 2368 adults between 15.12.2021 and 15.06.2022 using the snowball sampling method, which is one of the improbable sampling methods. Data were collected using “Personal Information Form, Munich Chronotype Questionnaire, Epworth Sleepiness Scale and Quality of Life Scale”.Results: 78.5% of the participants were Ara, 11.8% were Evening Chronotype, and 9.7% were Morning Chronotype; 29.2% had an Epworth Sleepiness score of ≥ 10; It was found that the mean score of the Physical Health Component of the Quality of Life Scale was 51.36±19.90 and the mean score of the Mental Health Component was 53.11±20.23. There was a negative correlation between the duration of using electronic devices before going to bed and the Chronotype type; A low level of positive correlation was found between Epworth Sleepiness Scale.Conclusion: The increase in the duration of electronic device use before going to bed at night was associated with a late chronotype, and daytime sleepiness increased, and the quality of life decreased as the duration of electronic device use before going to bed at night.
Keywords: Electronic device use; chronotype; daytime sleepiness; quality of life